What Make`s Patient Loyalty at Adi Husada Kapasari Hospital Surabaya? - Geonarso, Roberto A; Saputera, Ariawan Wangsa; Kurniawan, Afif (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2022)
Background: hospital is a comprehensive health service institution. In addition to curative and rehabilitative activities, hospitals also have promotive and preventive activities. Demand for health services increases along with population growth and the improvement of health services. The existence of the hospital is largely determined by the marketing strategy. A good marketing strategy will result in good patient loyalty. Every patient wants good and quality health services. Aims: This research was conducted at Adi Husada Kapasari Hospital to determine the relationship between brand image, service quality, and trust that has been built by the hospital on patient loyalty. Methods: The average number of outpatient visits was 70 patients. Then calculated the number of samples with simple random sampling and obtained a minimum sample of 49 people. This study used a cross-sectional method using a questionnaire and was conducted on the patient or the patient's companion. The independent variables in this study are brand image, service quality, and trust. dependent variable is patient loyalty. Results: The results of data collection showed that the level of patient loyalty was sufficient. The results of the spearman-rho test show that there is a relationship between brand image (0.604; 0.000), service quality (0.411; 0.000), trust (0.941; 0.000), and patient loyalty at Adi Husada Kapasari Hospital Surabaya. Conclusion: There is a relationship between brand image, service quality and trust on patient loyalty. Several studies have proven that the combination of these three independent variables will have an impact on the loyalty of consumers or service users. There needs to be an increase in service quality towards friendliness to patients. This is to improve the hospitality felt by patients at the Adi Husada Kapasari hospital.